Whole Genome Sequencing of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Escherichia coli Isolated From a Wastewater Treatment Plant in China - Jiang, Xiawei; Cui, Xinjie; Xu, Hao; Liu, Wenhong; Tao, Fangfang; Shao, Tiejuan; Pan, Xiaoping; Zheng, Beiwen (Frontiers in Microbiology, 2019)
Background and Objectives Wastewater treatment plants (WWTPs) are one of the major reservoirs for antimicrobial resistant bacteria (ARB) and antimicrobial resistance genes (ARGs) in the environment. Thus, the investigation on ARB and ARGs from WWTPs has attracted increasing attention in recent years. In order to uncover the resistome in a WWTP treating effluents from a pharmaceutical industry in China, the extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli strains were isolated and their whole genome sequences were obtained and analyzed. Moreover, metagenomic sequencing was applied to give a comprehensive view of antibiotic resistance in this WWTP. Methods 18 ESBL-producing E. coli strains were isolated from a WWTP located in Taizhou, China on April, 2017. All strains were sequenced using Illumina HiSeq 2000 sequencer. The whole genome sequences were assembled using SPAdes software and annotated with RAST server. Sequence types (STs), plasmids, ARGs and virulence genes were predicted from the genomes using MLST, Plasmid Finder, ResFinder and Virulence Finder, respectively. Metagenomic DNA of the same sample was extracted and sequenced using Illumina Hiseq X Ten platform. Metagenomic sequences were assembled using SOAPdenovo software. Results All 18 ESBL-producing E. coli strains were resistant to ampicillin, cefazolin, and ceftriaxone. Analysis of their genomes revealed that all strains carried beta-lactamase encoding genes and the most prevalent type was blaCTX–M. Various virulence genes and ARGs confronting resistance to other types of antimicrobial agents were also predicted. Further investigation on the metagenomics data indicated 11 ARGs with high amino acid identities to the known ARGs. Five of these ARGs, aadA1, aac(6′)-lb-cr, flo(R), sul2 and sul1, were also present in the genomes of the ESBL-producing E. coli isolated from the same sample. Conclusion Our study revealed the resistome of a pharmaceutical WWTP by both culture-dependent and metegenomic methods. The existence of ESBL-producing E. coli strains, indicating that pharmaceutical WWTP can play a significant role in the emergence of ARB. The occurrence of ARGs annotated from the metagenomic data suggests that pharmaceutical WWTP can play a significant role in the emergence of ARGs. Our findings highlight the need for strengthening the active surveillance of ARB and ARGs from pharmaceutical industry.